The Image of the Interpreter in the First Sino-Spanish Contacts (16th Century) - Béguelin-Argimón, Victoria (Sinología hispánica. China Studies Review, 2019)
The earliest Spanish travelers in China coming from the Philippines (16th century), not being able to communicate in Chinese, have to trust interpreters who, very often and for the most diverse reasons, do not always carry out their work with the expected fidelity. These interpreters, beyond being mere translators, also function as guides, as informants about the territory and, above all, as cultural mediators. The first documents on Sino-Spanish contacts, especially Rada’s, Loarca’s, Tordesillas’, and Sánchez’ travel accounts, written between 1575 and 1583, allow to catch a glimpse of the interpreters’ identity, their social and geographical origin, their linguistic and cultural skills, their various tasks in mediation as well as the difficulties they have to deal with in their work. The documents also allow to perceive the need for the first missionaries to learn Chinese and their very first attempts to do so.